Geospatial Information Technology Systems And Revenue Collection: The Case of Ilala City Council And Kinondoni Municipal Council (Tanzania Journal for Population studies and Development, 2023)
This study investigated the influence of critical success factors in boosting the performance of geospatial information technology systems (GITSs) in local government authorities. Data for was collected using a questionnaire involving business centres. Analysis was done using inferential statistics to analyse both primary and secondary data. The study employed a quantitative analysis approach, which was supported by two related concepts of diffusion of innovation and institutional theories: the technological, organizational, and environmental framework, and the technology acceptance model. The model was used to describe user perceptions, and actual geospatial information technology systems utilization, to acquire the perceptions of local government authorities, users and business license taxpayers. The study results revealed that technological, organizational and individual support are significant factors for enhancing geospatial information technology systems performance in local government authorities revenue collection, but their ranking is in the order T,O,P,S,E,I. The significance of this study is that it provides a credible approach, based on sound principles, for determining the most important factors that influence the performance of the applications of geospatial information technology systems within local government authorities.